Юннаны монголчуудын Чингис хааны тайлга тахилга: Chinggis khaan worship by Yunnan Mongols - С., Дулам (Mongolian Studies, 2023)
The cultural sphere of Mongolia is borderless; Mongolian culture will always exist anywhere a Mongol nation can sustain its culture and tradition. It is interesting to note that ancient Mongolian culture must have survived somewhere among the Mongol nations in the world. This is proven by the fact that Yunnan Mongols still worship Chinggis khaan, Munkh khaan and Hubilai khan through ritual practices.